Hey there!
Let's first solve g(x) when x = 3.
The first step is to change wherever it says x in the equation to 3, because that is the value we are solving for.
g(3) = 4(3) - 9
Next, we can multiply 4 by 3, because multiplication comes before subtraction in PEMDAS.
g(3) = 12 - 9
Lastly, we can subtract 9 from 12 to get the final value.
g(3) = 3 So, the value for g(x) when x = 3 is 3.
Now, we'll solve for g(x) when x = 5.
The first step is to change wherever it says x in the equation to 5, because that is the value we are solving for.
g(5) = 4(5) - 9
Next, we can multiply 4 by 5, because multiplication comes before subtraction in PEMDAS.
g(5) = 20 - 9
Lastly, we can subtract 9 from 20 to get the final value.
g(5) = 11 So, the value for g(x) when x = 5 is 11.
Hope this helps!